DEVELOPING ENGLISH SPEAKING SKILL FOR ACADEMIC PRESENTATION BASED ON GENRE BASED APPROACH FOR UNDER GRADUATE STUDENTS - Tongmak, Sirikarn; Onthanee, Angkana (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objective is to develop a new teaching method for effective genre-based approach in speaking English skills of undergraduate students. The sample groups were 60 undergraduate students collecting data from pre-test and post-test scores. The data were analyzed by percentage, mean, standard deviation and t-test independent sample. The findings were most of the students were 43 female or 70 percent and 18 male students or 30 percent. Most of the students, age between 20 and 24 years old, with 22 of 24 years old or 40 percent and had a GPA between 2.00-3.40, with the mode GPA 2.50 of 26 people, or 43.40 percent. A genre-based approach was applied to the students, it was found that post-test scores were increased from the pre-test in all aspects: behavior, fluency, grammar and vocabulary, organization. The test results showed a statistically significant increase and the teaching style of English according to the general-based approach consisted of 5 steps: 1) Selection of types of speech 2) Organizing language directory Vocabulary in each category, 3) making connections, making sentences, 4) speaking practice with body language, and 5) academic presentations.